(untitled) (Research, Society and Development, 2020)
The objective of this research was to identify, through bibliographic survey, academic and scientific productions which articulated the library and Professional and Technological Education. Searches were carried out at the Brazilian Digital Library of Theses and Dissertations (BDTD), Scientific Electronic Library Online (SciELO) and CAPES Journal Portal, using the descriptors: “Biblioteca Educação Profissional e Tecnológica” and “Educação” combined with “Library”, “Professional” and “Technology”. 27 articles and 49 dissertations were identified and analyzed through content analysis proposed by Bardin (2016), in the context of research with a qualitative approach. As a theoretical body, we highlight productions that interrelate Education, Work and Library, as well as Professional and Technological Education environments. The results of the present survey suggest that there is no discussion that orbits themes which articulate the Library and Professional Education. In addition, the research findings disregard formative, critical and present aspects in an informational unit, which appear as a possible gap in the literature in the educational area, which points to potential need for future studies and research.